Noonan syndrome‐like phenotype in a patient with heterozygous ERF truncating variant. (11th July 2021) - Yamada, Mamiko; Funato, Michinori; Kondo, Goro; Suzuki, Hisato; Uehara, Tomoko; Takenouchi, Toshiki; Sakamoto, Yoshiaki; Kosaki, Kenjiro
Abstract: Craniosynostosis is caused by abnormalities of multiple signaling pathways, including excessive RAS signaling. Recently, a truncating variant in ETS2 repressor factor ( ERF ), a negative transcriptional regulator of the RAS pathway, was shown to be associated with craniosynostosis. Here, we report a 10‐year‐old male patient with a heterozygous nonsense mutation, p.Arg183*, in ERF who exhibited craniosynostosis with Noonan syndrome‐like phenotypes. In consideration that loss‐of‐function variants in ERF would result in excessive RAS signaling and RASopathy phenotypes, we propose that ERF may represent a causative gene for Noonan syndrome. Since preceding studies on ERF mutations dealt with patients who were ascertained because of craniosynostosis, further studies are needed to evaluate whether patients with variants in ERF can present with Noonan syndrome‐like features without craniosynostosis.